2012
DOI: 10.29252/jnkums.4.2.145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Care Plan Based on the ROY ADAPTATION MODEL on Activities of Daily Living of hemodialysis Patients

Abstract: Background & Objectives:Saleint decrease in physical activity, including problems that are frequently observed in hemodialysis patients .Inversely, the performance level of hemodialysis patients related to with major health consequences such as health care costs and mortality. This study determined the Effect of Care Plan Based on the ROY ADAPTATION MODEL on Activities of Daily Living of hemodialysis Patients Material & Method: This clinical trial research was performed on 54 hemodialysis patients (28 interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
3
7
0
Order By: Relevance
“…This case indicated the effectiveness of RAM-guided education in the intervention group and in increasing their adaptation level in the physiologic mode. Similar results have also been reported in other studies which are in line with the results of this research ( 10 , 15 , 16 , 20 - 22 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This case indicated the effectiveness of RAM-guided education in the intervention group and in increasing their adaptation level in the physiologic mode. Similar results have also been reported in other studies which are in line with the results of this research ( 10 , 15 , 16 , 20 - 22 ).…”
Section: Discussionsupporting
confidence: 94%
“…RAM-guided education increases patients’ knowledge, better controls the situation, and consequently promotes the role function. Similar findings regarding the impact of nursing education on role function ( 10 , 15 , 16 , 20 - 22 ) confirm our finding.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this research showed effectiveness of the proposed educational plan in improvement of patients' ability in performing daily activities in intervention group, so that significant statistical difference was observed in intervention group before and after intervention while no significant statistical difference was observed in the control group before and after intervention. This finding is in line with the study conducted by ( 19 ) with titled using Roy model on daily activities of hemodialysis patients, the study of ( 23 ) conducted on daily activities of patients with MS using self-care program based on Orem's model and the study of ( 24 ) with title effects of antenatal education on maternal prenatal and postpartum adaptation. They found that using nursing theories has a positive effect on increasing ability to perform daily activities of patients' lives.…”
Section: Discussionsupporting
confidence: 88%
“…It is clear that adaptation of patients with the problems and long-term complications of disease play effective and significant roles in controlling the disease and promoting qualitative level of their life in all chronic diseases ( 14 , 19 ). Research findings indicated that educational plan based on Roy adaptation model can influence maladaptive behaviors of patients with heart failure in all physiologic, self-concept, role function and interdependence modes, so that significant reduction was observed in the number of maladaptive behaviors after intervention compared to before intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the several studies approve the results of this study. The results of the study by Amini et al 25 show that the positive effect of the Roy-based care program as an effective, lowcost, and noninvasive nursing intervention can reduce the fatigue in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%